"Never Hire Those—!" Hiring stigma in Turkish organizations: An exploratory sequential mixed methods approach. Issue 1 (12th April 2021) - Sever, Melih; Özdemir, Seyhan
Abstract: This mixed method study aims to analyze how stigma and discrimination operate in hiring processes. Although numerous studies address hiring stigma, extensive research and multiple factor measures in the Turkish and broader context are lacking. We employed an exploratory sequential mixed method design in this three‐phase study ( N = 423). Phase I was to analyze interviews from 23 employers/human resource managers in different sectors. Phase II was to develop a scale using findings to measure hiring stigma and to validate the scale, which is composed of 5 dimensions (people with criminal records, problematic alcohol and other drug use, disabilities, minority and/or nonconforming, and refugees) and 17 items. We then tested for discriminant and convergent validity on a different sample. Phase III was to administer the developed scale to a different sample in order to test factor analysis. Findings suggest that the hiring stigma scale is a valid and reliable measure and employers mostly stigmatize people with problematic use of alcohol and other drugs, people with criminal records, and refugees. We suggest organizing workshops, such as diversity trainings to increase awareness about stigmatizing attitudes of employers. Antidiscriminatory legislation should protect not only those with disabilities, but also other stigmatized groups at the state level.